Development of character education in families and communities in Indonesia - Qiyadah Robbaniyah; Roidah Lina; Dea Khalika Siregar; Khairinissa Zahrawani (At Turots: Jurnal Pendidikan Islam, 2024)
This study aims to analyze the application of local culture-based character education in several regions in Indonesia, as well as explore the values applied in families and communities. The research method used is a qualitative approach with data collection through in-depth interviews and observations of female students from various regions at the Tarbiyah Madani College of Sciences Yogyakarta. Data analysis is carried out through reduction, presentation, and conclusion drawn.  character education in various regions in Indonesia shows diversity in the values taught in accordance with their respective local cultures. In Java, character is formed through values such as discipline, honesty, and manners in the family, as well as social activities such as musafahah and mutual cooperation in society, which strengthen relationships between citizens. In Kalimantan, discipline, independence, and respect for others are taught in the family environment, while social activities such as mutual cooperation and fundraising in the community strengthen a sense of solidarity. Sumatra has traditions such as mutual cooperation in weddings and cultural festivals, which teach the value of cooperation, solidarity, and pride in local culture. Meanwhile, in NTB and NTT, the values of discipline, honesty, and cleanliness are taught in the family, with the community active in mutual cooperation and system to build a harmonious and safe environment. Overall, character education applied in various regions shows how local wisdom plays a role in shaping individuals who are responsible, caring, and respectful of social norms. These results indicate the importance of adapting cultural values in character education to create a generation that has strong moral, social, and cultural integrity in the midst of the influence of globalization.